2008
DOI: 10.1158/0008-5472.can-07-6341
|View full text |Cite
|
Sign up to set email alerts
|

The Side Population of Ovarian Cancer Cells Is a Primary Target of IFN-α Antitumor Effects

Abstract: The side population (SP), recently identified in several normal tissues and in a variety of tumors based on its ability to extrude some fluorescent dyes, may comprise cells endowed with stem cell features. In this study, we investigated the presence of SP in epithelial ovarian cancer and found it in 9 of 27 primary tumor samples analyzed, as well as in 4 of 6 cultures from xenotransplants. SP cells from one xenograft bearing a large SP fraction were characterized in detail. SP cells had higher proliferation ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 48 publications
7
112
0
Order By: Relevance
“…In a separate study, the SP fraction of a primary human EOC xenograft line, PDOVCA#1, was found to be more tumourigenic than the non-SP fraction (Moserle et al 2008). Interestingly, unsorted cells appeared more tumourigenic than either fraction alone.…”
Section: Sp Analysismentioning
confidence: 89%
“…In a separate study, the SP fraction of a primary human EOC xenograft line, PDOVCA#1, was found to be more tumourigenic than the non-SP fraction (Moserle et al 2008). Interestingly, unsorted cells appeared more tumourigenic than either fraction alone.…”
Section: Sp Analysismentioning
confidence: 89%
“…Compared with other ovarian cancer cells, ovarian CSCs have relatively high aldehyde dehydrogenase (ALDH1) enzymatic activity (9)(10)(11), which may serve to detoxify intracellular aldehydes or various cytotoxic drugs (12,13). Ovarian CSCs also can extrude small molecules, such as various chemotherapeutic drugs or fluorescent dyes, allowing for their identification as a less fluorescent "side population" in flowcytometric analysis of tumor cells stained with the DNA-binding dye Hoechst 33342 (14)(15)(16). Furthermore, ovarian CSCs may express various surface antigens, such as CD44, CD117, or CD133 (7,8,(17)(18)(19).…”
mentioning
confidence: 99%
“…We know that the expression of Oct-4 is restricted to the blastocyst stem cell population (inner cell mass, ICM). Following implantation, Oct-4 expression is limited to the epiblast compartment until gastrulation begins, as it is downregulated progressively using an anterior to posterior manner (86,87). Oct-4 expression is necessary in the maintenance of totipotency and synchronous division.…”
Section: Regulatory Mechanisms For Tumor Stem Cellsmentioning
confidence: 99%